Cropland encroachment on ecological land in Mainland Southeast Asia leads to massive carbon emissions - Danni Su; Kun Yang; Zongqi Peng; Run Sun; Mingfeng Zhang; Xiaofang Yang; Lusha Ma; Jingcong Ma (Ecological Indicators)
Mainland Southeast Asia (MSEA) is essential to the global carbon cycle. Balancing cropland expansion and ecological land protection amid population and economic growth is urgent. This study simulated MSEA’s land use patterns under SSP1-RCP2.6, SSP2-RCP4.5, and SSP5-RCP8.5 using the PLUS model with data from 1992 to 2022. Based on historical and future land use data and carbon density data for each land use type, the spatial and temporal changes in the encroachment of cropland on ecological land (E&C) and the resulting carbon emissions were analysed using the carbon stock loss method. The results showed that cropland encroached on 100,413.27 km2 of ecological land in MSEA over 30 years, causing 27.44 × 108 t of CO2 emissions, which accounts for 17.46 % of the total greenhouse gas emissions (data source: Our World in Data) in MSEA during the same period. Among these, Myanmar and Vietnam are the main contributing countries. Taking 2012 as the node, the E&C in MSEA is categorised into the early stage (1992–2012) and the late stage (2012–2022). Earlier, 57,253.86 km2 of ecological land was encroached, causing a carbon stock loss of 4.29 × 108t and 15.73 × 108t of CO2 emissions. Later, cropland encroached on 54,549.09 km2 of ecological land, causing a carbon stock loss of 4.03 × 108t and 14.81 × 108t of CO2 emissions. CO2 emissions from E&C accounted for 19.01 % and 18.44 % of total greenhouse gas emissions in the early and late stage, respectively. The largest carbon stock loss is in forests and shrublands. Under SSP1-RCP2.6, converting cropland to ecological land increases carbon stocks by 1.58 × 108t, offsetting 5.79 × 108t of CO2 emissions. However, under SSP2-RCP4.5 and SSP5-RCP8.5, carbon stocks decreased by 1.59 × 108t and 0.78 × 108t, leading to CO2 emissions of 5.83 × 108t and 2.87 × 108t, respectively. MSEA countries should adopt SSP1-RCP2.6, manage cropland expansion, balance economic development with ecological preservation, and strengthen international cooperation to address climate change.